Consumer protection in Muslim friendly travel agencies services - Ayob, Hamidah; Amin, Naemah; Ramli, Noriah (Kulliyyah of Languages and Management (KLM), International Islamic University Malaysia (IIUM), 2016)
Muslim friendly hospitality services have become increasingly important sector in the tourism industry in recent years. With the increasing number of Muslim travelers over the years, Malaysia has been listed as the world top Muslim friendly destination with 5.9 million Muslim tourists visited Malaysia in 2014. Despite this remarkable development, there have been many consumer complaints related to hospitality services in Malaysia. In fact, consumer claims against the travel agents were the top in the list of services cases filed in the Tribunal for Consumer Claims (TCC) for the past many years. In 2014, the TCC received 977 complaints against travel agencies especially related to umrah package. The question arises as to whether the rights of Muslim travellers are well protected under the relevant laws in Malaysia. Adopting the method of content analysis, this paper aims to discuss consumer protection issues in relation to travel and tour agencies services in Malaysia. The paper examines the adequacy of existing law in providing protection to Muslim travellers. The study discovers the lacunae in the existing legal protection which renders the protection to be inadequate. As such the study proposes improvement to the existing laws and practices so that it will be in line with shariah principles and to be able to provide adequate protection to the consumers in Muslim friendly tourism industry.